2016
DOI: 10.1038/ni.3588
|View full text |Cite
|
Sign up to set email alerts
|

E3 ubiquitin ligase RNF128 promotes innate antiviral immunity through K63-linked ubiquitination of TBK1

Abstract: TBK1 is essential for interferon-β (IFN-β) production and innate antiviral immunity. Here we identified the T cell anergy-related E3 ubiquitin ligase RNF128 as a positive regulator of TBK1 activation. RNF128 directly interacted with TBK1 through its protease-associated (PA) domain and catalyzed the K63-linked polyubiquitination of TBK1, which led to TBK1 activation, IRF3 activation and IFN-β production. Deficiency of RNF128 expression attenuated IRF3 activation, IFN-β production and innate antiviral immune res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
124
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(124 citation statements)
references
References 36 publications
0
124
0
Order By: Relevance
“…The phosphorylated state or expression level of TBK1 is precisely modulated by diverse regulators through post-translational modifications, such as phosphorylation, ubiquitination, deubiquitination, and SUMOylation. (28,30,(57)(58)(59)(60)(61)(62). For instance, protein phosphatase, Mg2 + /Mn2 + -dependent 1A and 1B, protein phosphatase 4, Raf kinase inhibitor protein, glycogen synthase kinase-3b, and glucocorticoids have been reported to modulate TBK1 activity through phosphorylation and dephosphorylation (63)(64)(65)(66)(67).…”
Section: Discussionmentioning
confidence: 99%
“…The phosphorylated state or expression level of TBK1 is precisely modulated by diverse regulators through post-translational modifications, such as phosphorylation, ubiquitination, deubiquitination, and SUMOylation. (28,30,(57)(58)(59)(60)(61)(62). For instance, protein phosphatase, Mg2 + /Mn2 + -dependent 1A and 1B, protein phosphatase 4, Raf kinase inhibitor protein, glycogen synthase kinase-3b, and glucocorticoids have been reported to modulate TBK1 activity through phosphorylation and dephosphorylation (63)(64)(65)(66)(67).…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggested that E3 ubiquitin, 26S protease, lysosomal, DEAD‐box helicase, hsp23.7, hsp 19.9 and lethal(2)denticleless‐like protein (p23 superfamily) were present in the MEbrown module. E3 ubiquitin ligase RNF128 promoted innate antiviral immunity (Song et al ., ), and DEAD‐box helicase DDX17 promoted antiviral defence (Moy et al ., ). In addition, hsp23.7 , hsp 19.9 and lethal(2)denticleless‐like protein, which belong to the small heat shock proteins (HSPs), were selectively induced in resistant silkworm after BmNPV infection.…”
Section: Discussionmentioning
confidence: 99%
“…After RNA binding, RIG-I activates mitochondrial antiviral signaling protein (MAVS; also known as VISA, IPS-1 and Cardif) on the mitochondrial membrane, which stimulates the polymerization of MAVS. As a scaffold protein, MAVS recruits various downstream effec-DOI: 10.1159/000489832 tors, such as TRAF2, TRAF6 and TRADD to form a "MAVS signalosome," which activates IκB kinase α and β (IKKα/β) and TANK-binding kinase 1 (TBK1) and IκB kinase ε (TBK1/IKKε) and leads to NF-κB and IRF3 activation [1]. STING (also known as MITA, MPYS, ERIS and TMEM173) was believed to play a central role as a DNA sensor and adaptor in the cytosolic DNA sensing pathways by directly engaging TBK1 to direct IRF3 activation [2].…”
Section: Introductionmentioning
confidence: 99%
“…The modification of TBK1 after dimerization at Lys30 and Lys401 by K63-linked polyubiquitin chains is required for TBK1 kinase activation [5]. Several E3 ubiquitin ligases, such as MIB1, MIB2, Nrdp1, and RNF128 were reported to be required for TBK1 activation by promoting K63-linked polyubiquitination [10][11][12]. Additionally, the E3 ubiquitin ligase DTX4 and TRAF-interacting protein have been shown to negatively regulate TBK1 activation by promoting proteasomal degradation of TBK1 [13,14].…”
Section: Introductionmentioning
confidence: 99%